Raw time results - Judt, David M.; Lawson, Craig P.; Lockett, Helen (Cranfield University, 2017)
Raw data for the wing D-nose aircraft system assembly time trials
Keywords: Aircraft assembly'; 'Wing systems'; 'Leading edge'; 'Time motion study'; 'Aircraft manufacturing'; 'Assembly orientation'; 'Assembly position'; 'Aerospace Engineering'